Genetic Diversity of Noroviruses Circulating in a Pediatric Cohort in Bangladesh. (23rd July 2018) - Nelson, Martha I; Mahfuz, Mustafa; Chhabra, Preeti; Haque, Rashidul; Seidman, Jessica C; Hossain, Iqbal; McGrath, Monica; Ahmed, A M Shamsir; Knobler, Stacey; Vinjé, Jan; Ahmed, Tahmeed
Abstract : Children in a birth cohort in Dhaka, Bangladesh, were frequently infected with noroviruses that were highly genetically diverse during their first 2 years of life, both during cases of diarrhea and during monthly collection when no diarrhea was present. Abstract: Noroviruses are a leading cause of diarrhea in children aged <5 years worldwide. We genotyped 88 viruses collected by active surveillance in a birth cohort of children <2 years of age in Dhaka, Bangladesh, during 2010–2013. Twenty-five of 31 (81%) established GI and GII genotypes were detected, with GII.4 as the predominant genotype (20%). Our results show that children in Bangladesh are infected with a great diversity of norovirus strains. Reinfections are common, but not with closely related genotypes. Birth cohort studies are critical to understand cross-protective immunity and advance the development of pediatric norovirus vaccines.